Shared-Use Decisions Among Administrators of Physical Activity Facilities in Pasadena, TX. Issue 6 (November 2020) - Stasi, Selina Marie; Spengler, John Otto; Maddock, Jay; McKyer, Lisako; Clark, Heather
Background and Purpose . The American Heart Association recommends community-based research on shared use of physical activity (PA) spaces. Pasadena, a community in southeast Houston, Texas with lower socioeconomic status and racial/ethnic diversity, was the setting for our study. Efforts to increase access to PA in Pasadena include building the evidence on PA resources. The purpose of this research was to utilize survey data in a community setting to inform and target efforts around sharing PA spaces. Method . An online survey was administered to K-12 school ( n = 25) and park ( n = 30) administrators, church leaders ( n = 10), community organizations ( n = 2), a health care center, and a local business. Results . Park facilities in Pasadena shared by agreement with two high schools and three baseball/softball leagues were ballfields, tennis courts, and jogging paths. No park facilities were shared with faith-based organizations. Four parks communicated daily, and five schools communicated with parks quarterly about providing opportunities for PA. Key facilitators to sharing facilities were building relationships and collaboration, service to the community, and improving health. Key barriers were cost, maintenance, staffing, and prioritizing use with limited time, facilities, and resources. Conclusions . This study is the first of its kind to address shared use at the community level and suggests opportunities to improve communication and partnerships between parks, schools, and churches. This research will inform ongoing efforts to promote access by identifying barriers and motivators among stakeholder groups to help facilitate shared use agreements.